Nottingham CityCare Partnership Stakeholder Analysis - Tarazi, Alexandra; Park, Jeena (2012)
This company report is a stakeholder analysis conducted on CityCare Nottingham Partnership, a social enterprise delivering NHS health and community services. It focuses particularly on CityCare's engagement with its patients, community, and staff.